Trajectories of cultural innovation from the Middle to Later Stone Age in Eastern Africa: Personal ornaments, bone artifacts, and ocher from Panga ya Saidi, Kenya. Issue 141 (April 2020) - d'Errico, Francesco; Pitarch Martí, Africa; Shipton, Ceri; Le Vraux, Emma; Ndiema, Emmanuel; Goldstein, Steven; Petraglia, Michael D.; Boivin, Nicole
Abstract: African Middle Stone Age (MSA) populations used pigments, manufactured and wore personal ornaments, made abstract engravings, and produced fully shaped bone tools. However, ongoing research across Africa reveals variability in the emergence of cultural innovations in the MSA and their subsequent development through the Later Stone Age (LSA). When present, it appears that cultural innovations manifest regional variability, suggestive of distinct cultural traditions. In eastern Africa, several Late Pleistocene sites have produced evidence for novel activities, but the chronologies of key behavioral innovations remain unclear. The 3 m deep, well-dated, Panga ya Saidi sequence in eastern Kenya, encompassing 19 layers covering a time span of 78 kyr beginning in late Marine Isotope Stage 5, is the only known African site recording the interplay between cultural and ecological diversity in a coastal forested environment. Excavations have yielded worked and incised bones, ostrich eggshell beads (OES), beads made from seashells, worked and engraved ocher pieces, fragments of coral, and a belemnite fossil. Here, we provide, for the first time, a detailed analysis of this material. This includes a taphonomic, archeozoological, technological, and functional study of bone artifacts; a technological and morphometric analysis of personal ornaments; and a technological and geochemical analysis of ocher pieces. The interpretation of the results stemming from the analysis of OES beads is guided by an ethnoarcheological perspective and field observations. We demonstrate that key cultural innovations on the eastern African coast are evident by 67 ka and exhibit remarkable diversity through the LSA and Iron Age. We suggest the cultural trajectories evident at Panga ya Saidi were shaped by both regional traditions and cultural/demic diffusion.